NEF'Î’S COUPLET OF A HERMENEUTIC OVERVIEW - Gülden SARI (Fırat University, 2019)
In this study, hermeneutic method has been applied for Nef’i's Dîvân of poem by a selected couplet. Functioning secular understanding of the unity of God went down to the deep structure of the surface structure of verse, leaving aside. Couplet has been pointed out to the allegorical meaning. Classical Turkish literature while text commentary are generally not exceeded the traditional attitude. This attitude, will cause the text to misunderstanding the various processes that occur. Hermeneutics, will facilitate the annotation of classical Turkish poetry. Classical Turkish poetry commentary make it easier for analysis according to the hermeneutics. For this purpose, the depth of meaning Nef’i's couplets were studied to be uncover. XVII. century classical Turkish poet who lived there before Nef'î. They write poetry before him. Şeyh Galip, Hafız-ı Şirazî and Nedîm of couplets were selected to be similar. Done analysis of common themes. Thus parallels shown. Selected couplets for Nef’î’s couplet, were examined in terms of both physical and metaphysical. It is also made of micro-universe expansion. Outside the poet's thoughts and feelings are the world connotations. Deep structure relationships unravel word was unveiled. The relationship between the dream world with the outside world were analyzed. Thus symbolic value in couplets were analyzed.